Utilizing a Guiding Catheter to Improve Endovascular Therapy Outcomes for Acute Vertebrobasilar Artery Occlusion in Patients with Tortuous Vessels - Himeno, Takahiro; Ohtonari, Tatsuya; Tanaka, Akio; Inoue, Tomoyuki; Koori, Ryuusuke; Sato, Kouta; Miyazaki, Takeshi; Ota, Shinzo (Asian Journal of Neurosurgery, 2024)
Objective Stable and swift placement of a guiding catheter in endovascular therapies for acute vertebrobasilar artery occlusion is often difficult because of the tortuous bends of the vertebral or subclavian artery especially in older people. The use of a delivery assist guiding catheter (DAGC) shortens the time with stable support to deliver a therapeutic treatment catheter to the target lesions. Herein, we reported the clinical and radiographic outcomes in endovascular therapies utilizing the DAGC for acute vertebrobasilar artery occlusions in actual clinical settings.Materials and Methods Between January 2018 and December 2021, 33 consecutive patients (males, 20[60.6%]; median age, 78 years) using a DAGC for acute vertebrobasilar artery occlusion were analyzed retrospectively. Reperfusion was graded using postinterventional angiograms based on the “thrombolysis in cerebral infarction” (TICI) classification. Furthermore, the time from puncture to recanalization and the rate of effective recanalization achievement were investigated.Results Effective recanalization with TICI 2b or 3 was achieved in 28 (84.8%) patients, and the median time from puncture to recanalization was only 44 minutes, despite the high rate of older patients in our cohort. In contrast, asymptomatic intracranial hemorrhage as a complication was observed in only 3 (9.1%) patients.Conclusion The DAGC contributes to the shortening of recanalization time and improves the outcomes of endovascular therapies for acute vertebrobasilar artery occlusion.
Keywords: acute vertebrobasilar artery occlusion; endovascular therapy; delivery assist guiding catheter; tortuous vessels; aspiration catheter